Describing the dynamics of recruits and juvenile scleractinian corals using 3d models: a case study from Cayo Mero reef, Morrocoy National Park, Venezuela - Mariño-Briceño, Gloria; Cappelletto, José; Ascanio, Alfredo; Agudo-Adriani, Esteban; Cróquer, Aldo (Novitates Caribaea, 2024)
Understanding the dynamics of coral recruitment and post-settlement is fundamental to a better comprehension of coral reef dynamics and recovery. We studied the abundance and survivorship of coral recruits and juveniles together with benthic dynamics at a scale of months and centimeters in Playa Mero reef, a disturbed reef in Morrocoy National Park. For this, we used photogrammetry to monitor eight permanent 50x50 cm quadrats haphazardly deployed every 3–4 months over 18 months. Juveniles and recruits of Agaricia spp. were at least four times more abundant than reef builders such as Orbicella spp. A distance-based linear model showed that rugosity, macroalgae, coral cover, and sand were the most important benthic variables and predicted up to 46% of the spatial and temporal variation of recruit and juvenile corals. The mortality of juvenile corals was higher than net recruitment rates, and only a limited number of genera such as Agariciids, Colpophyllia, Porites, and Scolymia were observed as recruits. Using a logit model, we also found a positive relationship between the mean growth rate and survivorship of juvenile corals (Nagelkerke R2= 0.67). We concluded the lack of recruitment of large reef builders, and the rapid mortality of a limited number of juvenile species, might be a sign of a coral community's failure to increase coral cover.